Addressing Women’s Economic Empowerment: An Analysis of Islamic Philanthropy Intervention Models and Their Effectiveness - Hidayati, Sri; AF, Cut Erika; Safitri, Gita; Nurwanti, Nurwanti (Ekonomis: Journal of Economics and Business, 2026)
This study investigates the effectiveness of intervention models employed by Islamic philanthropic organizations in Indonesia to economically empower women. Using a qualitative approach that integrates case studies, expert interviews, focus group discussions, and document analysis, the research examines programs led by Rumah Zakat, LAZ Harapan Dhuafa, BAZNAS, and LAZISMU. Findings reveal that successful models are holistic, multidimensional, and phased, integrating Sharia-compliant financial aid (e.g., qardh al-hasan), capacity building, technical mentoring, spiritual reinforcement, and market access facilitation. Quantitative evidence, such as a 96% Women’s Participation Index (IPP), a Gender Development Index (GDI) increase to 139.32, and a BAZNAS Welfare Index (BPI) score of 0.68, demonstrates significant impacts on poverty reduction, income growth, and enhanced female agency in household decision-making. However, challenges remain in scalability, dependency mindsets, and long-term impact measurement. The study concludes that Islamic philanthropy, with its integrated ethical and spiritual framework, offers a resilient and sustainable model for women’s economic empowerment, contributing substantially to the Sustainable Development Goals (SDGs), particularly in poverty alleviation, gender equality, and inclusive economic growth. This study contributes a refined framework for understanding the effectiveness of Islamic philanthropy, emphasizing the synergistic role of spiritual capital, digital inclusion, and ecosystem collaboration in achieving transformative women's economic empowerment.